2014
DOI: 10.1021/cm5004966
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cyclability of Li–O2 Batteries Based on TiO2 Supported Cathodes with No Carbon or Binder

Abstract: The decomposition of carbon materials and organic binders in Li−air batteries has been reported repeatedly in recent literature. The decomposition of carbon can harm the batteries' cyclability further by catalyzing electrolyte degrading. Therefore, there is a critical need to exploit a new catalyst support substituting carbon and develop a binder free cathode preparation strategy for Li−air batteries. Herein, TiO 2 nanotube arrays growing on Ti foam are used as the catalyst support to construct carbon and bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 33 publications
0
85
0
Order By: Relevance
“…Despite the possible decomposition of ether-based electrolytes, they are, to date, still the most studied in non-aqueous lithium/air systems. [85][86][87][88] …”
Section: Ether-based Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the possible decomposition of ether-based electrolytes, they are, to date, still the most studied in non-aqueous lithium/air systems. [85][86][87][88] …”
Section: Ether-based Electrolytesmentioning
confidence: 99%
“…In addition to these examples, there have been many other studies involving the use of metal catalysts in lithium/air batteries. [ 87,[184][185][186] Further studies are still needed to fi nd suitable ways to develop stable and selective catalysts for the desired reactions.…”
Section: Metalsmentioning
confidence: 99%
“…[1][2][3][4] However, the development of practical Li-O 2 batteries faces several serious challenges, including high overpotential between charge and discharge, poor cycling stability, low Coulombic efficiency and low rate capability. [5][6][7][8] The reaction mechanism in a Li-O 2 cell involves an oxygen reduction reaction (ORR) in the discharge process and an oxygen evolution reaction (OER) in the charge process, during which molecular O 2 reacts reversibly with Li + ions (Li + +O 2 +2e − ↔ Li 2 O 2 , with an equilibrium voltage of 2.96 V vs Li). 9,10 This mechanism is very different from the traditional intercalation reactions of Li-ion batteries.…”
Section: Introductionmentioning
confidence: 99%
“…So far, it has been identified that catalysts and appropriate non-aqueous electrolytes can effectively overcome these problems. 6,7,12 Various catalysts, such as metal oxides, metal nitrides and noble metals have been investigated as suitable cathode catalysts in Li-O 2 cells to reduce the charge overpotential. [13][14][15] The use of catalysts can decrease the charge potential to~3.8 V from~4.2 V. 9,16,17 Therefore, finding suitable cathode catalysts is an effective approach to solve the overpotential problem.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 To circumvent these issues, electrically conductive metal oxides are promising materials due to their inherent stability against oxidation. Hence, the magnéli phase Ti 4 O 7 28 as well as Pt supported on TiO 2 nanofibers 29 have been proposed as eligible compounds for Li-O 2 cathodes.…”
mentioning
confidence: 99%